Parent–adolescent communication on sexual and reproductive health issues and associated factors among secondary public-school students in Gondar town, northwest Ethiopia: an institution based cross-sectional study - Melese, Mihret; Esubalew, Dereje; Siyoum, Tsehayu Melak; Worku, Yilkal Belete; Azanaw, Jember; Mengistie, Berihun Agegn (Frontiers in Public Health, 2024)
Adolescent-parent communication on sexual and reproductive health issues and associated factors among secondary government school students in Gondar town, northwest Ethiopia, 2023 Manuscript Id: 1342027